Burden and factors associated with work-zone crashes on an interurban highway in Pakistan. (1st March 2011) - Bhatti, J A; Razzak, J A; Lagarde, E; Salmi, L
Abstract : Introduction: Highway work zones (HWZ) may lead to an increased road traffic crash (RTC) risk. Little is known about such crashes in low-income countries (LICs). Objective: To assess burden and factors associated with HWZ crashes on a highway in Pakistan. Methods: Police reported crashes occurring on Karachi-Hala road-section from Jan 2006 to Dec 2008 were included in this study. We compared crash and death risk between work and normal traffic zones for a 50-km-long road-section for which data was available on work zone dates and average daily traffic. Crash locations were described for a further 146-km-long section on which we assessed factors associated with HWZ crashes. Results: Of 180 crashes, 27 (15%) occurred in HWZs accounting for 30.8% of road fatalities (N=91). HWZ exposition was one-sixth of the whole traffic exposition on the selected road section. Rates were higher in HWZ compared to other parts of the road for crash (RR)=2.28, (95% CI 1.14 to 4.56), attributable risk (AR)=18.5%) and death (RR=4.56, 95% CI 2.05 to 10.16, AR=39.0%). Opposite-direction (adjusted OR (aOR)=8.01, 95% CI 2.34 to 27.68) and RTCs on wet surfaces (aOR=10.43, 95% CI 1.38 to 79.15) were significantly associated with HWZ crashes. Conclusion: These results indicate that traffic separation in work-zones should be prioritised to reduce the increased burden of crashes in LICs.